The Relationship of Self-Efficacy, Sensation Seeking and Coping Sterategies with Aptitude of Substance Use in University Students - Azar Kiamarsi; Abbas Abolghasemi (Drug Control Headquarters, Research and Education Office, 2012)
Introduction: The purpose of the research was to determine relationship of coping sterategies, self-efficacy and sensation seeking with aptitude of substance use in the students. Method: The population of the study included students of Islamic Azad University Ardabil Branch. The research sample consisted of 313 students who were studying in Islamic Azad University Ardabil Branch. To collect the data Coping Sterategies scale, Sensation Seeking scale, Self-Efficacy inventory and Substance Use Aptitude scale were used. Data was analyzed using of Pearson correlation coefficient and multiple regression analyses. Findings: The result of Pearson correlation coefficients showed that self-efficacy, sensation seeking, emotin coping sterategies and problem solving coping sterategies related to aptitude substance use in students. The results of multiple regression analysis showed that self-efficacy, sensation seeking and coping sterategies explained 43 percent of variance of aptitude of substance use in students. Conclusion: The results indicated that self-efficacy, sensation seeking and coping sterategies are significant predictors in predicting of aptitude of substance use in adolescents. Clinicians can be used these results for prevention of substance abuse by training of effective coping strategies and promotion of self efficacy.